2021
DOI: 10.1063/5.0027599
|View full text |Cite
|
Sign up to set email alerts
|

Denoising electron holograms using the wavelet hidden Markov model for phase retrieval—Applications to the phase-shifting method

Abstract: Noise reduction using the wavelet hidden Markov model (WHMM) was applied to electron holograms of a LaFeO3/SrTiO3 specimen, which was subjected to phase retrieval by the phase-shifting method. A systematic study revealed the optimal conditions regarding the electron dose and number of holograms used for phase retrieval, for which the effect of denoising was most pronounced. The denoised holograms revealed the magnitude of the phase shift at the LaFeO3/SrTiO3 interface, while the original, noisy holograms did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Indeed, the sensitivity during phase analysis depends on the image quality of holograms composed of the interference fringes of electron waves ( 22 ). To solve this problem, we used several methods, including hologram acquisition with negligible mechanical and electrical disturbances using a sophisticated 1.2-MV atomic-resolution holography microscope ( 23 ) with an aberration corrector and reduction of the statistical noise using a wavelet hidden Markov model (WHMM) ( 24 , 25 ). As described below in detail, the holography observations enabled counting of just a few charges responsible for the electric charging in a single supported NP.…”
mentioning
confidence: 99%
“…Indeed, the sensitivity during phase analysis depends on the image quality of holograms composed of the interference fringes of electron waves ( 22 ). To solve this problem, we used several methods, including hologram acquisition with negligible mechanical and electrical disturbances using a sophisticated 1.2-MV atomic-resolution holography microscope ( 23 ) with an aberration corrector and reduction of the statistical noise using a wavelet hidden Markov model (WHMM) ( 24 , 25 ). As described below in detail, the holography observations enabled counting of just a few charges responsible for the electric charging in a single supported NP.…”
mentioning
confidence: 99%
“…Starting from the initial paths that can be initially identified cumulatively, the library of all paths is subjected to probabilistic calculations and the state correlations between the sets are described after the final results are derived. Furthermore, since the Hidden Markov Model does not have an associated memory condition, only the previous state phase with the highest similarity to that state can be projected [15]. It is also shown that the probability of a particular predicted path occurring in the malicious attack path prediction method is most highly correlated with the last solution in the set of posterior variants of the sensor node.…”
Section: Designing Malicious Attack Path Prediction Methodsmentioning
confidence: 99%
“…The user behavior prediction of the proposed method is mainly based on a set of hidden Markov models [22], [23]. First, relevant machine learning methods are used offline to train the prediction model parameters of various behaviors from historical data; Then, according to the partial behaviors of current online users, a finite step Markov process prediction is performed to obtain a relatively complete sequence of user behaviors; Finally, this behavior sequence is used to guide the push of university archives business data.…”
Section: User Behavior Predictionmentioning
confidence: 99%